Retrieving Examination Results Through Wireless Application Protocol - Husen, Mohd Nizam (2006)
Students who are taking examinations in any learning institution would like to know their results as soon as it is available. The widely used of mobile phone among students in higher learning institution could be exploited as a medium for retrieving the examination results. They may retrieve the results anytime and anywhere through their mobile device by activating General Packet Radio Service (GPRS) or using Wireless Fidelity (WiFi) technology. This paper presents the whole process for the development of a Mobile Web Application to retrieve examination results using mobile devices through Wireless Application Protocol (WAP). The process includes developing requirement model, prototype construction and usability testing. The objectives of the study are to develop the requirement models of a mobile web application in retrieval of examination results using WAP technology; and to evaluate the prototype using usability testing. The application is proposed for the usage of the students in Malaysian Institute of Information Technology, Universiti Kuala Lumpur (MIIT UniKL). The methodology that has been used is Rational Unified Process (RUP) and the techniques used for usability testing are think aloud protocol and semi-structured interviews. The usability testing that has been conducted in this research revealed that the WAP application in retrieval of examination results is effective, easy to use, well-accepted by students and should be implemented for MIIT UniKL.